2018
DOI: 10.1371/journal.pone.0195802
|View full text |Cite
|
Sign up to set email alerts
|

The somatostatin receptor 2 antagonist 64Cu-NODAGA-JR11 outperforms 64Cu-DOTA-TATE in a mouse xenograft model

Abstract: Copper-64 is an attractive radionuclide for PET imaging and is frequently used in clinical applications. The aim of this study was to perform a side-by-side comparison of the in vitro and in vivo performance of 64Cu-NODAGA-JR11 (NODAGA = 1,4,7-triazacyclononane,1-glutaric acid,4,7-acetic acid, JR11 = p-Cl-Phe-cyclo(D-Cys-Aph(Hor)-D-Aph(cbm)-Lys-Thr-Cys)D-Tyr-NH2), a somatostatin receptor 2 antagonist, with the clinically used sst2 agonist 64Cu-DOTA-TATE ((TATE = D-Phe-cyclo(Cys-Tyr-D-Trp-Lys-Thr-Cys)Thr). In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…4) is most probably due to free radionuclides, because macrocyclic copperchelates can suffer from limited in vivo stability against superoxide dismutase in the liver (21). Rylova et al reported that 64 Cu-DOTA-TATE is more stable in humans than in mice (22). It is possible that 64 Cu-or 225 Ac-labeled FAPI-04 shows a different biodistribution in humans, especially for liver uptake.…”
Section: Table 1 Whole-body Distribution After Intravenous Administramentioning
confidence: 99%
“…4) is most probably due to free radionuclides, because macrocyclic copperchelates can suffer from limited in vivo stability against superoxide dismutase in the liver (21). Rylova et al reported that 64 Cu-DOTA-TATE is more stable in humans than in mice (22). It is possible that 64 Cu-or 225 Ac-labeled FAPI-04 shows a different biodistribution in humans, especially for liver uptake.…”
Section: Table 1 Whole-body Distribution After Intravenous Administramentioning
confidence: 99%
“…The hypothesis of a ligand rebinding mechanism has been put forward, but this still requires some investigation before it can be validated. These first results were confirmed by preclinical studies and by preliminary clinical trials and seems to show superior results for antagonist-based tracers than agonists [ 218 , 219 , 220 , 221 ]. The first comparative study of antagonists with Octreoscan ® confirmed the good characteristics of the [ 111 In]-DOTA-BASS analog, and better accumulation at the level of the tumor and better visualization of metastases.…”
Section: Antagonists Vs Agonistsmentioning
confidence: 75%
“…The earliest time point for quantitative imaging after injection of labelled abatacept in mice is thus 24 h. We chose 48 h to guarantee equilibrated distribution and as 48 h provided better imaging results than 18 h in our former study with the related protein 111 In-DOTA-belatacept [20,21]. For labelling, we chose Cu-64 as it provides high spatial resolution due to its low decay energy (0.7 mm mean range in water before annihilation) and as 64 Cu-NODAGA complexes have an excellent stability in vivo [36][37][38]. The physical (radioactivity decay) half-life of 12.7 h resulted in signal loss of 9 90 % within the 48 h between tracer injection and imaging.…”
Section: Discussionmentioning
confidence: 99%